Deskriptif Kemiskinan di Kabupaten Gorontalo Ditinjau dari Pendidikan, Pertumbuhan Penduduk, dan Investasi Daerah - Dewi Walahe; Fantrida S. Garusu; Marlin Ina; Nensa Karim; Moh. Anasrullah Wonggo (Jurnal Ilmu Administrasi Negara, 2026)
Poverty remains a key development challenge in Gorontalo Regency and is influenced by education, population growth, and regional investment. This study analyzes the development of these factors and their relationship to poverty levels from 2018 to 2023. A descriptive quantitative method was applied using secondary data from Statistics Indonesia (BPS), analyzed through descriptive tables and graphs without causal modeling.Results show a gradual decline in poverty in line with increasing average years of schooling, highlighting the role of education in improving welfare. Population growth consistently increased, posing potential socio-economic pressure if not matched with employment opportunities. Regional investment, measured by GFCF, also rose after 2020, though its direct impact on poverty reduction has not yet been significant in the short term. This study emphasizes the importance of strengthening education and planning development based on demographic and investment dynamics. Future research is encouraged to use longer datasets and inferential methods